2022
DOI: 10.54393/pjhs.v3i07.284
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Mothers Regarding Malnutrition in Children Under Five Years Old in Muzaffargarh

Abstract: Malnutrition is still a serious issue that mostly affects children under the age of five worldwide, not just in impoverished nations. Early on in life, ensuring that children get the nutrients they need is critical to their immune system health, as well as their physical and intellectual growth Objectives: To explore the perception of mothers regarding malnutrition in children under five years old in Muzaffargarh. Methods: This was a descriptive qualitative study carried out in Muzaffargarh, Punjab. Overall 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the similar context, other studies also provided similar ndings and reported that recurrent diarrhea among the children lead to severe loss minerals and electrolytes. This not only affects the children current health status but also lead to severe malnutrition [31,32].…”
Section: Poor Sanitation Systemmentioning
confidence: 99%
“…In the similar context, other studies also provided similar ndings and reported that recurrent diarrhea among the children lead to severe loss minerals and electrolytes. This not only affects the children current health status but also lead to severe malnutrition [31,32].…”
Section: Poor Sanitation Systemmentioning
confidence: 99%